Persuasive Communication Strategies Used by Physical Education, Sports, and Health Teachers in Increasing Students' Learning Motivation - Mansur Mansur; Ashabul Yamin Asgha; Masri Masri (Proceedings of AICS - Social Sciences, 2021)
The learning process consists of a combination of tactics, procedures, and approaches that have been incorporated to transmit information from teachers to students. Persuasive communication strategy is one of the strategies that teachers may use to improve students' learning motivation in physical education, sports, and health courses. This study employs a descriptive qualitative technique that focuses on a single case study to explain the phenomena under investigation. All previously selected informants were subjected to data collecting procedures involving in-depth interviews. The sampling technique used is purposive sampling. The data collected were analyzed qualitatively. The results found that persuasive communication increased students'' learning motivation. The teacher used varied strategies namely, using association techniques, techniques to integrate communicator abilities, reward techniques, and arrangement techniques, or icing techniques. The strategy used in communicating with students is through association, integration, reward and arrangement communication techniques or the icing technique. The use of persuasive communication strategies by teachers is the right and the most effective way to increase students'' learning motivation to enhance students’ cognitive, affective, and psychomotor domains.Keywords: Persuasive communication; Physical Education, Sports, and Health Teachers (PESHT); student motivation.